Unpacking the Disruption Process: New Technology, Business Models, and Incumbent Adaptation - Cozzolino, Alessio; Verona, Gianmario; Rothaermel, Frank T. (Journal of Management Studies, 2018)
AbstractDespite the growing importance of digital transformation and the notion of disruptive innovation, strategy literature still lacks a more complete picture of how incumbent organizations adapt their business models after disruptions. This research sheds light on this important process by analyzing a major Italian news media publisher reacting to the advent of the internet and the emergence of new business models by entrants into the industry (1995–2017). We specifically examine: (1) the drivers and impeding factors of business model adaptation; (2) how incumbents change strategies to cope with different components of the disruption process; and (3) how a closed business model can be renewed to develop an open, platform‐based business model to seize external opportunities, incur lower costs, and fend off disruptors. This study contributes to the burgeoning literature on disruption, business models, and platforms.